TINGKAT PEMAHAMAN MAHASISWA KEGURUAN TERHADAP PERANGKAT PEMBELAJARAN KURIKULUM MERDEKA - Pratomo, Laurensia Claudia; Fattah, Fuad Abdul (Universitas Negeri Makassar, 2024)
One of the primary goals of teacher education programs is to produce qualified educators. As aspiring teachers, students must be capable of designing effective learning materials. These materials should be tailored to meet the specific needs of their students and align with the principles of the current curriculum. The Independent Curriculum has recently replaced the 2013 Curriculum. This study aimed to assess the extent of undergraduate student’s understanding of how to develop learning materials based on the Independent Curriculum. Employing a quantitative research design, data was collected through a brief quiz focused on Independent Curriculum-related topics. Participants were third-year students enrolled in the Economics Education program at Jenderal Soedirman University. The findings revealed that these undergraduate student as pre-service teachers faced several challenges in developing learning materials. Notably, they exhibited a limited understanding of key components within the Learning Goal Pathway, such as Learning Achievement and Learning Objectives. Furthermore, the students struggled to grasp the concept of the Pancasila Student Profile, a new feature of the Independent Curriculum. The students also perceived significant differences between the assessment methods used in the Merdeka Independent and those employed in the 2013 curriculum.